Robert Kilwardby's Disputational Logic. Issue 3 (2nd July 2016) - Thom, Paul
Abstract : The article is concerned with the account of Aristotle's theory of disputation given by Robert Kilwardby (d. 1279) in his commentary, composed in Paris during the 1240s, on Aristotle's Prior Analytics . Specifically, I show that Kilwardby covers demonstrative as well as dialectical disputations, and gives an elementary account of the rules governing such disputations, in their adversarial forms as well as in an idealized form where the interlocutors engage in a cooperative activity. I describe the resemblances and the differences between disputations as theorized by Kilwardby and the game of obligationes as understood by some of his contemporaries.